Resilient capacity of Malaysian schools’ headteachers in adversity: A review - Puspa Liza, Ghazali; Ahmad Firdause, Md Fadzil; Nik Hazimi, Mohammed Foziah; Hamidah, Che Abdul Hamid; Eni Noreni, Mohamad Zain; Sukono, .; Abdul Talib, Bon (2021)
Educational leaders faced twin challenges of responding to unprecedented community needs while managing radical changes within their own organizations and across the ministry of education plan and action. Within a few weeks in March 2020, education in Malaysia changed with unimaginable speed and scope, paralleling earlier experiences across the world. The pandemic amplified the urgency of action taken in education sector. Face to face learning is at stake, curriculum has been simplified and public examination for primary school was postponed. Somehow school leaders especially primary schools need to manage the school effectively. Multiple decisions needed to be made, communicated, implemented, and managed which need resilience capacity. In this article, we describe some key resilient elements identified and lessons from experiences as primary school headteachers during this time and within the future to foresee. We draw some experienced from the six high-performing primary school headteachers in Malaysia and two from the expertise. There were broad criteria of resilient leaders in primary schools. The criteria fall into categories of leadership whereby resilience capacity within the school leaders towards the school organization, parents, community and stakeholders have to be considered. The consequences of these responses resulted in a renewed recognition for school leaders to be resilient and ingenuity of teachers and primary school students. We provide examples of these lessons, themes and make recommendations for how to manage the school in the “new normal’ of living with COVID-19 and global challenges to be prepared with the unprecedented incident which might happens in modern times.